Evolution and Hotspot Analysis of Ecological Compensation Research in Watersheds - Wang Huaiyi; Li Zhongkui (Shuitu baochi tongbao)
[Objective] The research status of watershed ecological compensation was analyzed and mastered in order to provide a basis for improving the compensation system and promoting watershed ecological protection and high-quality development of river basins in China. [Methods] CiteSpace visualization software, Price's law, and the X index were used to analyze 876 studies collected by CNKI for author co-occurrence, high-frequency keywords, and research topic clustering. [Results] Domestic research on watershed ecological compensation mainly began in 2000, and the annual number of publications showed an upward trend. Research hotspots were highly coupled with national policies and watershed development, mainly including quantitative research on watershed ecological compensation standards, research on the behavior of watershed ecological compensation subjects from the perspective of game theory, and research on watershed ecological compensation mechanisms under the background of ecological protection. According to the evolution characteristics of research topics, three stages could be identified: preliminary exploration (before 2007), rapid development (2007—2017), and consolidation and improvement (from 2018 to 2021). During these time periods, research emphasis changed from theoretical analysis to quantitative analysis of compensation standards under the background of water resource governance. The objective of this research focused on the two major water systems of the Yangtze River basin and the Yellow River basin. Researches on the main stream and important tributaries were carried out alternately and gradually deepened. The researches formed multiple basic scientific research platforms, but there were few high-yield authors and little cross sectoral cooperation. [Conclusion] Over the past 20 years, research in the field of watershed ecological compensation in China has formed a certain theoretical system and research framework. The research topics and hot spots have distinctive characteristics, and the research methods have tended to be systematic and diversified. In the future, theory and application should be combined to explore the dynamic and market-oriented compensation mechanisms suitable for regional characteristics.